2019
DOI: 10.1186/s12935-019-1017-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-346 inhibits the growth of glioma by directly targeting NFIB

Abstract: BackgroundGlioma is considered one of the most common tumors and has a poor prognosis. Recently, microRNAs (miRNAs) have been reported to be strongly linked to various human tumors including glioma. In this study, we investigated a new anticancer miRNA, miR-346, to determine the effects and mechanism of miR-346 and its downstream target gene NFIB on tumors.MethodsLentivirus transfection, real-time PCR, western blotting, immunohistochemistry, cell proliferation assays, and mouse experiments were used to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…NFIB is a member of the nuclear factor family (which also includes NFIA, and NFIX). Emerging evidence has demonstrated that NFIB could not only participate in normal somatic development [22], it also acted as an oncogene and involved in tumorigenesis of several cancers, including osteosarcoma [23], glioma [24], astrocytoma [25], gastric cancer [26], breast cancer [27]. Liu et al's research showed that NFIB could suppress p21 transcription [28].…”
Section: Discussionmentioning
confidence: 99%
“…NFIB is a member of the nuclear factor family (which also includes NFIA, and NFIX). Emerging evidence has demonstrated that NFIB could not only participate in normal somatic development [22], it also acted as an oncogene and involved in tumorigenesis of several cancers, including osteosarcoma [23], glioma [24], astrocytoma [25], gastric cancer [26], breast cancer [27]. Liu et al's research showed that NFIB could suppress p21 transcription [28].…”
Section: Discussionmentioning
confidence: 99%
“…4 l). Meanwhile, Yangyang Li et al[ 32 ] reported that miR-346 directly targets NFIB to inhibit the growth of glioma cells. In order to verify whether miR-346 could directly target NFIB in CRC cells, we constructed two pmirGLO vectors, one containing the 3′UTR of NFIB (wild type, WT) and the other one with the miR-346-binding site mutated (MUT) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we utilized four online bioinformatics prediction databases to predict potential target genes of miR-346. NFIB appeared in all four databases and has been reported as a target gene of miR-346 in glioma [32]. Moreover, NFIB was identified as an oncogene in CRC [31,43].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, circDDX17 was able to act as a sponge for miR-346 such as to promote the levels of LHPP. Meanwhile, some targets of miR-346 have been reported in other studies and included NDRG2, YTHDF1, GSK-3β, and NFIB [31][32][33][34]. However, potential target(s) of circDDX17/miR-346 were not heretofore reported upon in the literature.…”
Section: Discussionmentioning
confidence: 94%